Levensbeschrijving van Prof. Mr. B.M. Telders, door C.S. Telders, A.W. Abspoel, L. Erades [e.a. Met voorw. van N.E.H. van Esveld. Ten geleide van R.P. Cleveringa] (Nijhoff, 1972)
Uitg. onder auspiciën van de Prof. Mr. B.M. Teldersstichting.